Brain SPECT in mesial temporal lobe epilepsy: comparison between visual analysis and SPM - Amorim,Bárbara Juarez (2010)
OBJECTIVE: To compare the accuracy of SPM and visual analysis of brain SPECT in patients with mesial temporal lobe epilepsy (MTLE). METHOD: Interictal and ictal SPECTs of 22 patients with MTLE were performed. Visual analysis were performed in interictal (VISUAL(inter)) and ictal (VISUAL(ictal/inter)) studies. SPM analysis consisted of comparing interictal (SPM(inter)) and ictal SPECTs (SPM(ictal)) of each patient to control group and by comparing perfusion of temporal lobes in ictal and interictal studies among themselves (SPM(ictal/inter)). RESULTS: For detection of the epileptogenic focus, the sensitivities were as follows: VISUAL(inter)=68%; VISUAL(ictal/inter)=100%; SPM(inter)=45%; SPM(ictal)=64% and SPM(ictal/inter)=77%. SPM was able to detect more areas of hyperperfusion and hypoperfusion. CONCLUSION: SPM did not improve the sensitivity to detect epileptogenic focus. However, SPM detected different regions of hypoperfusion and hyperperfusion and is therefore a helpful tool for better understand pathophysiology of seizures in MTLE.